KERJASAMA DAN KEKOMPAKAN SISWA DALAM PEMBELAJARAN FISIKA DI KELAS XI MIPA SMA NEGERI 3 KOTA JAMBI - Putri, Amalla Rizki; Maison, Maison; Darmaji, Darmaji (EduFisika: Jurnal Pendidikan Fisika, 2018)
The problem when researcher was observed is the learning oriented for outcomes. That is make students competition each other even though cooperation and student cohesiveness needed when learning physics subjects because physics subjects considered difficult. This the purpose of this research is to know cooperation and student cohesivenss in class when physics subjects. The research for 268 respondent that is from 7 class of XI MIPA SMAN 3 Kota Jambi. The method of research is descriptive with quantitative approach. The data collection technique use questionnaire with two scale that is cooperation and student cohesiveness. The descriptive statistics used for data analysis. The results is cooperation in class when learning physics subjects including â€œvery goodâ€ category with average value of 4,20 on maximum value of 5 and standard deviation value of 0,84. Student cohesiveness in the class when learning physics subjects including â€œgoodâ€ category with average value of 3,86 on maximum value of 5 and standard deviation value of 0,88.